2014
DOI: 10.1111/bph.12607
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of the cannabinoid CB2 receptor in stress‐induced neuroinflammation in mice

Abstract: BACKGROUND AND PURPOSEStress exposure produces excitotoxicity and neuroinflammation, contributing to the cellular damage observed in stress-related neuropathologies. The endocannabinoids provide a homeostatic system, present in stress-responsive neural circuits. Here, we have assessed the possible regulatory role of cannabinoid CB2 receptors in stress-induced excitotoxicity and neuroinflammation. EXPERIMENTAL APPROACHWe used wild type (WT), transgenic overexpressing CB2 receptors (CB2xP) and CB2 receptor knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 64 publications
7
68
0
Order By: Relevance
“…A final possibility is that loss of Cnr2 contributes to epileptogenesis by enhancing inflammation, as CB2 receptors are widely expressed throughout the immune system, and suppress peripheral immune function upon activation . Cnr2 −/− mice have increased inflammation in response to stress, whereas transgenic overexpression of Cnr2 was neuroprotective . Inflammatory changes are hypothesized to contribute to epileptogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…A final possibility is that loss of Cnr2 contributes to epileptogenesis by enhancing inflammation, as CB2 receptors are widely expressed throughout the immune system, and suppress peripheral immune function upon activation . Cnr2 −/− mice have increased inflammation in response to stress, whereas transgenic overexpression of Cnr2 was neuroprotective . Inflammatory changes are hypothesized to contribute to epileptogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…More data come from preclinical studies, which reported a reduction of CB2 receptors in the hippocampus, striatum and midbrain in animal models of depression. Similarly, an increase of CB2 receptor expression counteracts behavioural and neurochemical features related to a depressive-like state [105][106][107]. Other controversial data about the endocannabinoid brain content in depression have also been recorded.…”
Section: Cannabis Endocannabinoid System and Depression: Clinical Anmentioning
confidence: 99%
“…17 CB2R is involved in neuroinflammation and the CB2R agonist, JWH-133, mitigates stress-related neuroinflammation-dependent pathologies. 18,19 Selective activation of peripheral cannaboid receptors is appealing because it would avoid neuropsychiatric adverse effects associated with activation of CB1R in the central nervous system. Sickle mice display neurogenic inflammation and hyperalgesia via a mast-celldependent mechanism.…”
Section: Introductionmentioning
confidence: 99%